A revision of Japanese Epuraeinae (Coleoptera, Nitidulidae). Part I. Epuraea subgenera: Dadopora Thomson, Epuraea Erichson, and Epuraeanella Crotch - Hisamatsu, Sadatomo (Zootaxa, 2016)
Three subgenera of Epuraea: Dadopora Thomson, Epuraea Erichson, and Epuraeanella Crotch, are revised for Japan. Thirty-six species are recognized. The following six are new records for Japan: Epuraea (Epuraea) laferi Kirejtshuk; E. (E.) melina Erichson; E. (E.) pygmaea (Gyllenhal); E. (E.) quadrangula Motschulsky; E. (E.) reichardti Sjöberg; and E. (Dadopora) vicaria Kirejtshuk & Kvamme. The following species are synonymized: E. (E.) hisamatsui Nakane with E. (E.) rufomarginata (Stephens) syn. nov.; and E. (E.) alpicola Nakane with E. (E.) terminalis (Mannerheim) syn. nov. The following two species are removed from the Japanese fauna: E. (Dadopora) fuscicollis (Stephens) and E. (E.) longula Erichson; the former was erroneously recorded as E. fuscicollis (Stephens, 1835) by Kashizaki & Hisamatsu (2011), and the latter is corrected as E. (E.) pseudorapax Kirejtshuk. The following three species are described as new: E. (E.) apiciclara sp. nov.; E. (E.) camura sp. nov.; and E. (E.) foramina sp. nov. Dorsal habitus, antenna, protibia, male and female genitalia, internal sac sclerites of male genitalia, and other important diagnostic characters of all species are illustrated. Keys are presented to Epuraeinae tribes, genera, subgenera, and Epuraea species of in the following subgenera: Dadopora, Epuraea, and Epuraeanella.